The concept of an architectural solution for the service intended to build an enterprise strategy map - Moskalenko, Valentina Volodymyrovna; Berezenko, Yuriy Stanislavovich (НТУ "ХПИ", 2017)
The article examines an architectural solution of a software application for building an enterprise strategy map. It gives a short review of existing software products at the IT-market, which is used in strategic enterprise performance management. Much attention is dedicated to the separate stage of the development program formation, i.e. strategy map building. For building such a map it is proposed to formulate general enterprise strategic goals on the basis of an analysis of the development direction priorities and then check them for their feasibility. Next, the selected goals are decomposed into goals by the perspectives in accordance with the balanced storecard. The goals are analyzed for the impact of key success factors. Based on the success factors, bunch of strategic key performance indicators are formed. The paper examines problems that need to be solved at each stage of the map building, and proposes mathematical methods for their solving such as the analytic hierarchy process, the trajectory approach in conjunction with the system optimization and the cognitive analysis. The author suggests using service-oriented architecture for EPM-system implementation and microservice architecture for the implementation of the strategic map application. As result the study identifies four services that implement the following business functions: an identification of priority directions for the enterprise development and general strategic goals; a verification of the feasibility of common strategic goals and planned targets formation; a definition of the goals by the perspectives, KSF definition and building of the strategy map; a definition of KPI by the perspectives. The structure of the software application is presented as a component diagram.

Предлагается архитектурное решение программного обеспечения для задачи построения стратегической карты предприятия, приведен процесс построения стратегической карты и методы, используемые при решении задач на этапах этого процесса. Приведен краткий обзор существующих на IT-рынке программных продуктов, используемых в стратегическом управлении. Сделаны выводы о целесообразности использовать сервис-ориентированную архитектуру для программной реализации отдельных модулей системы стратегического управления и микросервисную архитектуру для моудля стратегической карты предприятия.
Концепция архитектурного решения для сервиса построения стратегической карты предприятия
Keywords: стратегическое планирование; корпоративная информационная система; микросервис; ключевые показатели деятельности; strategic planning; corporate information system; microservice; key performance indicators